Kalibrasi Sensor TDS Menggunakan Metode Regresi Linear untuk Sistem Kontrol Nutrisi Hidroponik Berbasis IoT - Dava Abi Wardhana; Achmad Solichan; Aris Kiswanto (Jurnal Teknik Informatika dan Teknologi Informasi, 2025)
Modern agriculture faces increasingly complex challenges that demand innovative technological solutions to improve efficiency, precision, and sustainability. The Internet of Things (IoT) offers significant potential for agricultural automation, particularly in hydroponic cultivation systems. This study presents the design and development of an IoT-based automatic nutrient control and monitoring system for vertical hydroponics. The system utilizes an ESP32 microcontroller to regulate the distribution of nutrient solutions enriched with essential macro- and micronutrients. Nutrient concentration is measured as Total Dissolved Solids (TDS) and monitored in real time through the Blynk mobile application. Users can operate the system in either automatic or manual mode. Experimental results show that the developed prototype achieves high accuracy in TDS measurement, with an average accuracy of 97.38%, and effectively maintains nutrient concentration within the desired range. The proposed system demonstrates reliable control performance and contributes to enhancing nutrient delivery precision, productivity, and land-use efficiency in modern smart farming practices.